2014
DOI: 10.1371/journal.pone.0101933
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of C5 Palsy following Posterior Cervical Decompression: A Systematic Review

Abstract: BackgroundC5 palsy is a serious but poorly understood complication after posterior cervical decompression that could lead to muscle weakness, brachialgia and numbness of the upper limbs. The incidence of C5 palsy varies greatly between studies. The risk factors are inconclusive and even conflicting.ObjectTo perform a systematic review on the incidence and risk factors of C5 palsy after posterior cervical decompression.Materials and MethodsFour databases, PubMed, Embase, Web of Science and Cochrane CENTRAL, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 38 publications
2
75
1
Order By: Relevance
“…11,12 Although many studies on C5 palsy after posterior cervical surgery have been published, the results are often inconclusive and even conflicting. 13,14 Here, we provide a systematic review of the current literature and attempt to analyze the conflicting results among studies to better understand the clinical features, influencing factors, and preventive measures of C5 palsy after posterior cervical surgery.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Although many studies on C5 palsy after posterior cervical surgery have been published, the results are often inconclusive and even conflicting. 13,14 Here, we provide a systematic review of the current literature and attempt to analyze the conflicting results among studies to better understand the clinical features, influencing factors, and preventive measures of C5 palsy after posterior cervical surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, if posterior shift of the cord is not sufficient, ventral constriction of the cord may persist, leading to decreased recovery from myelopathy. Some authors have recognized the complications of this procedure, including axial pain and C5 root palsy [8][9][10]. Further, some studies have reported that patients who undergo posterior laminoplasty or laminectomy are more likely to suffer from cervical kyphosis or instability than those who receive treatment via anterior approaches [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Wang et al [17] noted that ACDF using a stand-alone cage was associated with significantly less blood loss compared with a posterior approach, while operative time was similar for both procedures. A previous study shows that C5 nerve root palsy is more likely to happen in patients who undergo posterior decompression compared with ACDF following excessive spinal cord drift after laminectomy [24]; postoperative C5 palsy may also associate the presence of C4-5 high intensity cord signal changes or a long duration of symptoms [25]. In the meta-analysis by Shou et al [26], the highest prevalence of C5 palsy was noted among the patients who had laminectomy and fusion (11.0%), in contrast to (3.3%) in the ACDF group.…”
Section: Discussionmentioning
confidence: 98%